Neo-Tethyan subduction triggered Eocene–Oligocene magmatism in eastern Iran. (14th March 2023) - Omidianfar, Siavash; Monsef, Iman; Rahgoshay, Mohammad; Shafaii Moghadam, Hadi; Cousens, Brian; Chen, Ming; Rajabpour, Shahrokh; Zheng, Jianping
Abstract: Eocene–Oligocene magmatic rocks are well exposed in the region south of Birjand, eastern Iran. The ages, geochemistry and petrogenesis of these rocks are important to understand eastern Iran's magmatic and geodynamic history during the Cenozoic. Detailed field investigations show that numerous intrusive, intermediate to felsic units are intruded into a thick sequence of Eocene–Oligocene lava flows and their accompanying pyroclastic rocks. The volcanic rocks are mainly basaltic andesitic to rhyolitic, whereas intrusive rocks are characterized by dioritic to granitic composition. Previously compiled U–Pb geochronological data indicate that Eocene–Oligocene magmatism in eastern Iran formed continuously from ∼46 Ma to ∼25 Ma. Our new zircon U–Pb data reveal crystallization ages of 43.6 ± 0.4 Ma to 39.5 ± 0.6 Ma, consistent with the upper end of this age range. Geochemically, the igneous rocks have high-K calc-alkaline to shoshonitic signatures. Rare-earth and trace element patterns show enrichment in LREEs, K, Rb, Cs, Pb, Th and U and depletion in HFSEs such as Nb, Zr and Ti, typical of a subduction-related environment. 87 Sr/ 86 Sr(i) and ϵNd(i) values range from 0.7051 to 0.7064 and −0.1 to +0.2, respectively. We postulate that the Cretaceous northeastward subduction of the Neo-Tethyan oceanic lithosphere underneath the Iranian Plateau caused sub-continental lithospheric mantle (SCLM) metasomatism by slab-derived fluid components. Subsequently, slab roll-back of the Neo-Tethyan oceanic lithosphere associated with asthenospheric upwelling led to lithospheric thinning and melting of the metasomatized SCLM. The resulting parental magmas probably interacted with upper continental crust during magma ascent to form Eocene–Oligocene magmatism in eastern Iran.